2019
DOI: 10.1016/j.jhazmat.2019.01.069
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating a novel permeable reactive bio-barrier to remediate PAH-contaminated groundwater

Abstract: Permeable reactive barriers (PRBs) are an environmentally-friendly, cost-effective insitu technology that can be used to remediate polycyclic aromatic hydrocarbons (PAHs)-contaminated groundwater. In this study, PRB of two various materials (A and B) that relied on microbes self-domestication mechanism were designed and tested. The materials A and B were the same apart from their carbon source: A was based on wheat straw and B was based on coconut shell biochar. We used laboratory batch experiments followed by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(24 citation statements)
references
References 68 publications
0
24
0
Order By: Relevance
“…Coconut shell biochar pellets (coconut shell biochar combined with diatomite, attapulgite, and CaO 2 ) were used to construct Bio-PRBs for the treatment of PHE-contaminated groundwater . Compared to that of wheat straw pellet Bio-PRBs (0.013 mg g –1 ), the PHE adsorption capacity (0.035 mg g –1 ) increased by 169% in coconut shell biochar Bio-PRBs . The biochar-immobilized microorganism and ZVI gel beads were developed to construct Bio-PRBs for the treatment of 2,4,6-TCP-contaminated groundwater .…”
Section: Advances In Bio-prb Technologymentioning
confidence: 99%
“…Coconut shell biochar pellets (coconut shell biochar combined with diatomite, attapulgite, and CaO 2 ) were used to construct Bio-PRBs for the treatment of PHE-contaminated groundwater . Compared to that of wheat straw pellet Bio-PRBs (0.013 mg g –1 ), the PHE adsorption capacity (0.035 mg g –1 ) increased by 169% in coconut shell biochar Bio-PRBs . The biochar-immobilized microorganism and ZVI gel beads were developed to construct Bio-PRBs for the treatment of 2,4,6-TCP-contaminated groundwater .…”
Section: Advances In Bio-prb Technologymentioning
confidence: 99%
“…Other than ZVI, many other materials have been tested for in situ remediation of groundwater contaminated with halogenated organics, phenolic compounds, pharmaceuticals, and nitroaromatics (Guan et al, 2015). For instance, zeolite (Vignola et al, 2011), calcite (Turner et al, 2008), pyrite (Wang et al, 2020), combined calcium peroxide and straw/biochar (Liu et al 2019) have been used or tested as PRB filling materials. In addition, biochar (Tang et al, 2013), mackinawite (FeS) (Jeong and Hayes, 2007;Duan et al, 2019b), FeS-modified ZVI (Duan et al, 2019a;Kim et al, 2011;, and MnO 2activated persulfate (Mazloomi et al, 2016) have been tested to remediate soil and groundwater contaminated with organic pollutants.…”
Section: G R a P H I C Abstract Abstractmentioning
confidence: 99%
“…Yin et al (2012) reported that the presence of certain organic substrates improved the removal rate of p-NCB with microbes by promoting a bio-reduction process. In a previous study, our group accessed the potential of wheat straw as an additional carbon source for the remediation of groundwater contaminated with phenanthrene (Liu et al, 2019). As a continuation of that prior work, the present research examined the role of wheat straw as a carbon and energy source to promote the biological reductive dechlorination of o-NCB.…”
Section: Introductionmentioning
confidence: 97%